The Influence of Parental Attitudes Toward Entrepreneurship on Individual Entrepreneurial Decisions in Thailand - Watanapalin, Noraniti (2020)
This study investigates the role of parental attitudes and cultural influences on the family environment in the formation of entrepreneurial intention in Thailand. The study was conducted because Thailand is a paradox in entrepreneurial theory: even though it has a strongly collectivist culture, which typically reduces entrepreneurial activity, it has one of the highest rates of entrepreneurship and business ownership in the world. This raises the question of why this has occurred, which this study posits has its roots in the family environment. The objectives set for the research include: 1) to explore attitudes of parents and adult children toward an entrepreneurship career; 2) to explore the influence of parental attitudes toward entrepreneurship on the adult child’s decision to become an entrepreneur; and 3) to examine whether a strong family bond culture influences the decision to become an entrepreneur, particularly for an entrepreneurial family. These objectives were accomplished using a qualitative research design. Interviews were conducted with parents and adult children from three entrepreneurial families and three non-entrepreneurial families (n =18). These interviews were analysed using thematic analysis. The findings show that entrepreneurial parents typically have a more positive attitude toward entrepreneurship than non-entrepreneurial parents, but the attitudes of adult children from these families is similar. Attitudes of entrepreneurial adult children also vary from their parents. Parental attitudes do influence adult children’s decisions to become entrepreneurs, but this influence may not always be positive, especially if children and parents disagree or parents try to exert too much control. Family bonds and collectivism do influence willingness to help in the family business, as part of the child’s perceived filial duty, but do not strongly influence either entrepreneurial intentions or intention to take over the family business in future. There are some implications of these findings for both academic research and government policy.